Gambaran Tingkat Pengetahuan Perawat terhadap Penggunaan Metode Electronic Medical Record (EMR) Di Ruang Rawat Inap Rumah Sakit Mardi Rahayu Kudus - Indah kurniawati; Yayuk Fatmawati (Indonesian Journal of Nursing Research (IJNR), 2022)
Background : Electronic medical record had one of the big challenges in the application of information and communication technology in hospitals. The definition of electronic medical records varies, however, in principle had used of a database to record all medical, demographic data and every event in patient management in hospitals and clinics (Cassano, 2018). The development of knowledge is so fast, nurses will quickly be left behind if they do not take advantage of various things to update the latest developments. Given how important medical records are, it is necessary to make progress in terms of knowledge of the application of electronic medical records. Digital recording of medical records must be known how the recording system is and need to be developed in order to promote more effective and efficient health services so as to reduce the incidence of medical errors. In addition, the development of an integrated nursing information system is the main strategy to facilitate nurses in carrying out nursing care documentation.Purpose: The aim of this research was to describe the level of knowledge of nurses on the use of the Electronic Medical Record (EMR) method in the Inpatient Room of the Mardirahayu Hospital, Kudus.Methods: This research used quantitative with a descriptive research design. The research population is the number of nurses in the inpatient room at the Mardirahayu Kudus Hospital, namely 156 nurses. The research sample is 61 nurses, with non probability sampling technique with stratified random sampling method. The instrument of this research used questionnaire on the nurses knowledge using by Electronic Medical Record (EMR).Results: The results showed that respondents had sufficient knowledge as many as 34 respondents (55.7 %), while good knowledge as many as 24 respondents (39.3%), and lack of knowledge as many as 3 respondents (4.9.1%).Conclution: Most of the respondents have sufficient knowledge of the use of electronic medical records (EMR) in the inpatient ward of Mardi Rahayu Kudus Hospital, as many as 34 respondents (55.7%).